Tendencies and Regularities of Russian Regional Transport Systems’ Development - Berezhnoy, Vladimir Ivanovich; Berezhnaya, Olga Vladimirovna; Kosenko, Svetlana Gennadievna; Matevosian, Maria Gendrihovna; Berezhnaya, Elena Viktorovna (International Journal of Economics and Financial Issues, 2015)
The article describes the methodological approach to the analysis of trends and regularities of development of regional transport systems (RTS), the estimation of the degree of influence of the spatial socio-economic system of the state of the RTS was conducted, using the authorial complex models of correlation and regression analyzes, allowing to identify the determinants of their functioning within the context of the Federation groups of factors, determining the functioning and formation of RTS as a structural part and economic space in the region, and industry sector. The author emphasizes the specific features of the RTS as a subsystem of spatial socio-economic system. As a part of the methodological foundations of RTS research, author highlights the main elements of the analysis, justified the use of the integral characteristics of the RTS (risk and efficiency) as the key ones for a strategic planning and the basis for their calculation is discussed in details – methods of analysis of the spatial development of the RTS. Keywords: regional transportation systems, comparative analysis, correlation and regression analysis, spatial socio-economic system, regional socio-economic system. JEL Classifications: H54; R41; R42; Z13